Data reduction scheme for measuring GIIc of wood in end-notched flexure (ENF) tests - Moura, M.F.S.F. de
Numerical and experimental studies of end-notched flexure (ENF) fracture tests were performed to obtain mode II R curves for maritime pine (Pinus pinaster Ait.) wood in the radial-longitudinal (RL) crack propagation system. Three- (3D) and two-dimensional (2D) finite element analyses were conducted to determine the mode II release rate of the critical strain energy (GIIc). The 3D analysis revealed that a small spurious mode III component did not affect GIIc measurements and that the 2D model was very accurate. A new scheme for data reduction based on the equivalent crack concept is proposed to overcome the difficulties related to accurate crack length measurement during propagation. This method does not require previous experimental tests to obtain the elasticmodulus, which varies markedly for different wood specimens. Experimental ENF tests were performed to verify the numerical results. The results demonstrate the accuracy of the data reduction method proposed.